Psychological Distress among Parents due to Their Children Having Cancer: A Systematic Review - Nurhidayah, Ikeu; Dewi, Ratih Kusuma; Hidayati, Nur Oktavia; Poddar, Sandeep (Kesmas, 2022)
As a result of their children's cancer, parents are at risk of experiencing psychological distress. Parental stress will affect their roles in providing emotional support for their children. This systematic review aimed to identify the psychological distress of parents having children with cancer. EBSCO, PubMed, Science Direct, and Research Gate were applied to conduct electronic searches. The terms "parents," "children," "cancer," and "psychological distress" were combined using the Boolean expressions "OR" and "AND." The inclusion criteria were non-experimental studies published in English within the last 10 years (2010- 2020). Risk of bias assessment was conducted for each included study using the Joanna Bridge Institute critical appraisal tools to build transparency of findings. A total of 12 articles were included in the study to determine the prevalence of psychological distress among parents and the symptoms and factors that influence it. The high category of parental distress reached 17.6%, while the very high category reached 5.8%. Thus, it needed more concern. Suicidal ideation, insomnia, and poor health were all connected to psychological distress, with the age of children and parents, the number of children, occupation, education level, depressive history, and time of diagnosis all being predictive factors